Edukasi Masyarakat Dalam Meningkatkan Pengetahuan Tentang Penyakit Hepatitis Akut Misterius Di Kelurahan Tanjung Merdeka Kota Makassar - Sididi, Mansur; Andi Nurlinda; Een Kurnaesih (Window of Community Dedication Journal, 2022)
In developed countries outbreaks often run very slowly, outbreaks with a "common source" pattern can spread quickly. Outbreaks due to the "Common source" pattern of transmission are related to food contaminated by food handlers and contaminated food products. The purpose of this activity is to increase public knowledge regarding acute hepatitis and how to prevent it. The method used in this activity is in the form of lectures, discussions and demonstrations. With a sample of 20 residents. The results obtained after the counseling that has been carried out is that the level of knowledge of residents increases about acute hepatitis and how to prevent it. Suggestions to residents are expected to disseminate information that has been obtained to other communities.